Temporal trend in non-melanoma skin cancer mortality in China, 1992–2021: an analysis for the global burden of disease study 2021 - Li, Deng; Yan, Ge; Song, Shasha; Fan, Siqi; Zhao, Haochen; Hu, Gang; Xu, Xuewen; Li, Qingfeng (Frontiers in Medicine, 2025)
IntroductionNon - melanoma skin cancer (NMSC) is a widespread malignant neoplasm affecting the skin globally. In China, over the past 30 years, the prevalence and incidence of NMSC have changed significantly, yet mortality rate (MR) data is scarce. The aim is to assess the MR data of NMSC patients worldwide from 1992 to 2021, analyze its temporal trends, and provide valuable epidemiological information for future prevention and management strategies of NMSC.MethodsUsing data from the Global Burden of Disease Study 2021 (GBD 2021), we analyzed crude mortality rate (CMR), age-standardized mortality rate (ASMR), and sex- and age-specific mortality trends, with temporal patterns assessed through longitudinal comparisons.ResultsThe MR for NMSC has shown an upward trend globally. From 1992 to 2021, both the CMR and ASMR for NMSC have increased substantially. The global ASMR has risen by approximately 30% during this period. Males have a higher ASMR compared to females, and the elderly population exhibits an accelerated and elevated ASMR trend for NMSC. In China, the mortality of NMSC is on the rise, with the current male MR exceeding that of females. Although the ASMR is projected to decline by 2030, the number of mortality cases is expected to increase, especially among males. The MR for NMSC shows a significant bias towards the elderly demographic.DiscussionThe increasing mortality of NMSC, both globally and in China, highlights the importance of effective prevention and management strategies. In addition to implementing prevention and intervention measures in susceptible populations, it is crucial to establish a screening framework for NMSC to detect minor symptoms in a timely manner. This will help in early diagnosis and potentially reduce the mortality rate associated with NMSC. Thank you for your editorial support.